Chemical and mechanical reprocessed resins and bio-composites based on five epoxidized vegetable oils thermosets reinforced with flax fibers or PLA woven - Di Mauro, Chiara; Genua, Aratz; Rymarczyk, Monica; Dobbels, Caroline; Malburet, Samuel; Graillot, Alain; Mija, Alice (Composites science and technology, 2021)
Bio-epoxy resins based on five epoxidized vegetable oils were formulated with an aromatic disulfide crosslinker with diacid functionality, 2,2′-dithiodibenzoic acid (DTBA), to obtain recyclable epoxy thermosets. Flax fibres (FF) and PLA woven were used as bio-based reinforcements for these matrices. Different percentages of reinforcement were tested and the effect of the natural fibres on the matrix's crosslinking reaction was studied by DSC analysis. Then, the obtained materials were analyzed by Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA), Dynamic Mechanical Analysis (DMA), water absorption and Scanning Electron Microscopy (SEM). The reinforcements improved the thermal and mechanical properties of the neat resins, with tan δ values varying from 91 to 148 °C showing a good compatibility matrix-FF but a reduced one in case of matrix-PLA woven. The dynamic nature of the networks crosslinking allowed the chemical and mechanical recycling of both resins and bio-composites. Moreover, the obtained results show the possibility to recuperate the natural FF filler for the preparation of second-life generation bio-composites. [Display omitted]